Left Circumflexus Coronary Artery Total Occlusion with Clinical Presentation as NSTEMI and Acute Pulmonary Oedema - Budi Yuli Setianto; Nahar Taufiq; Heri Hernawan (Interna Publishing, 2017)
Current guidelines for the management of patients with acute coronary syndromes (ACSs) focus on the electrocardiogram to divide patients into ST-elevation acute myocardial infarction (STEMI) or non-ST-elevation acute myocardial infarction (NSTEMI)/unstable angina (UA). Patients with STEMI in the earliest time will receive reperfusion therapy to destruct occlusive thrombus. An ST segment elevation is the 'sine qua non' for diagnosing acute total coronary occlusion causing transmural myocardial infarction. Left circumflex coronary artery (LCx) occlusion is often categorized as NSTEMI because of the absence of significant ST-elevation on the 12 lead standard electrocardiogram. An ST segment elevation is presented in fewer than 50% of patients with LCx total occlusion, such that the reperfusion therapy is delayed. We reported a 77 years old woman whom being diagnosed with NSTEMI because a 12 lead electrocardiogram showed ST segment depression in lead V2-V5. On coronary angiography, we found a total occlusion in the LCx artery as the culprit lession.